Driving Societal Change: Occupational Therapy, Health and Human Rights - Hocking, C; Townsend, E; Galheigo, SM; Erlandsson, L; Mesquita Chagas, JN (World Federation of Occupational Therapists (WFOT), 2014)
Introduction: Many UN and WHO documents assert the relationship between health and human rights. Both organizations acknowledge that addressing the right to health will require societal change to meet the needs of people who live in poverty, particularly women and girls. How can occupational therapists respond to this call to action?
Keywords: Occupational therapy education; Vulnerable groups in society; Occupational rights